Disseminated tuberculosis and gastric mucormycosis coinfection. (2019) - Malek, Alexandre; De la Hoz, Alejandro; Arduino, Roberto; Aisenberg, Gabriel M.
Abstract: Tuberculosis and mucormycosis coinfection has rarely been reported in the medical literature. We present a case of gastrointestinal (GI) mucormycosis in a diabetic patient with disseminated tuberculosis. Early diagnosis, addressing the risk factors for mucormycosis, surgical debridement, and timely antifungal treatment are the mainstay of care.